Pricing computational resources in a dynamic grid. (6th August 2009) - Abdelkader, Khalid; Broeckhove, Jan
In this paper, we investigate the pricing of resources in dynamic grids. Particularly, we investigate grid resource management based on a computational commodity market of CPU resources. The prices of these resources are determined based on achieving supply-and-demand equilibrium. This approach has been shown to work for small grids with a static fabric. Using simulations, we show that this approach can be extended to grids with thousands of resources and to grids with a dynamic fabric.